2020
DOI: 10.1186/s12968-019-0596-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-existing cerebrovascular atherosclerosis predicts subsequent vascular event: a multi-contrast cardiovascular magnetic resonance imaging study

Abstract: Background: It is still unknown that whether co-existing intracranial stenosis and extracranial carotid vulnerable plaques have higher predictive value for subsequent vascular events. This study aimed to determine the relationship between co-existing extracranial carotid vulnerable plaques and intracranial stenosis and subsequent vascular events utilizing cardiovascular magnetic resonance (CMR) vessel wall imaging. Methods: Patients who had recent cerebrovascular symptoms in anterior circulation (< 2 weeks) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Also, the use of 3D black blood MRI can potentially detect more plaques without stenosis than DSA (up to 27% more by a recent study) (Tian et al, 2021 ). Recent 3D MR-VWI studies showed that the total plaque number involving both the symptomatic intracranial and extracranial arteries had a strong predictive value for recurrent stroke (Xu et al, 2016 ; Li et al, 2020 ). Compared to previous studies, our study with 3D MR-VWI evaluated the entire cerebral vasculature out to the second-order branches, rather than only the symptomatic arterial territory; our approach enriched the existing evidence that multiple intracranial plaques are related to stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the use of 3D black blood MRI can potentially detect more plaques without stenosis than DSA (up to 27% more by a recent study) (Tian et al, 2021 ). Recent 3D MR-VWI studies showed that the total plaque number involving both the symptomatic intracranial and extracranial arteries had a strong predictive value for recurrent stroke (Xu et al, 2016 ; Li et al, 2020 ). Compared to previous studies, our study with 3D MR-VWI evaluated the entire cerebral vasculature out to the second-order branches, rather than only the symptomatic arterial territory; our approach enriched the existing evidence that multiple intracranial plaques are related to stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Many large prospective studies have documented that the presence of multiple intracranial atherosclerotic stenoses (ICAS) or concurrent extracranial atherosclerosis, on computed tomography angiography (CTA) (Lau et al, 2013 ), magnetic resonance angiography (MRA) (Man et al, 2009 ; Wang et al, 2014 ; Sun et al, 2018 ), or digital subtraction angiography (DSA) (Zhao et al, 2018 ), was an independent predictor of stroke recurrence. Coexisting cerebrovascular atherosclerosis involving both intracranial and extracranial arterial beds is an independent predictor for subsequent vascular events (including ischemic stroke) (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] However, most of these studies were cross sectional and there has been little investigation into the prognostic value of HR-MRI. 10,11 In addition, a previous study investigating changes in plaque features over time and their relationship to recurrent stroke was limited by small sample size (N < 15). 12 Thus, the aim of this study was 1) to investigate the prognostic value of intracranial atherosclerotic plaque features in predicting recurrent cerebrovascular ischemic events using HR-MRI in acute stroke patients and 2) to evaluate the temporal changes of plaque features and study their relationship to recurrent ischemic events.…”
mentioning
confidence: 99%
“… 5 , 6 , 7 , 8 , 9 However, most of these studies were cross sectional and there has been little investigation into the prognostic value of HR‐MRI. 10 , 11 In addition, a previous study investigating changes in plaque features over time and their relationship to recurrent stroke was limited by small sample size ( N < 15). 12 …”
mentioning
confidence: 99%
“…A previous study found that the coexistence of intracranial artery stenosis and the extracranial lipid-rich necrotic core was associated with a higher risk of subsequent vascular events. 18 We aimed to test the hypothesis that concurrent intracranial atherosclerotic stenosis (ICAS) and extracranial atherosclerotic stenosis (ECAS) might increase the risk of stroke recurrence and composite vascular events in patients with transient ischaemic symptoms or AIS with negative DWI.…”
Section: Introductionmentioning
confidence: 99%